Tuberculum Sellae Meningioma Resection: Technical Nuances on the Frontopterional Approach - Rustemi, Oriela; Scienza, Renato; Della Puppa, Alessandro (Journal of Neurological Surgery Part B: Skull Base, 2018)
Tuberculum sellae meningioma remains a surgical challenge. Deep location of tumor, vascular and nerve encasement, and pituitary stalk involvement are the main technical issues. The frontopterional approach represents a natural, simple, and elegant approach to this area enabling surgeon to have a direct control on all anatomical structures. A 42-year-old woman was referred with a delayed diagnosis of tuberculum sellae meningioma due to the presence of HLA-B27-associated uveitis. She presented with 1/10 visual acuity in the left eye and no right visual function. A left frontopterional craniotomy was performed. Visual function improved postoperatively. The video illustrates the cisternal anatomy via pterional approach.The link to the video can be found at: https://youtu.be/Hmbf5bt7A64.
Keywords: tuberculum sellae meningioma; pterional approach; cisternal anatomy; optic canal